A Closer Look on the Main Characters Tendency: BUMI MANUSIA by Pramoedya Ananta Toer - Gari, Nelia; Herdi, Herdi; Agus, Ichsan J.M. H. T.; Putri, Wella C.; Pradina, Siska (Universitas Malikussaleh, 2019)
A novel is a story that is related to real or fictional events imagined by the author through their observation of reality. The analysis of this present article aims to describe the magnitude of the characterization effect through a character figure and the position of the characters in the novel